2010
DOI: 10.1371/journal.pone.0011127
|View full text |Cite
|
Sign up to set email alerts
|

Lethal Thermal Impact at Periphery of Pyroclastic Surges: Evidences at Pompeii

Abstract: BackgroundThe evaluation of mortality of pyroclastic surges and flows (PDCs) produced by explosive eruptions is a major goal in risk assessment and mitigation, particularly in distal reaches of flows that are often heavily urbanized. Pompeii and the nearby archaeological sites preserve the most complete set of evidence of the 79 AD catastrophic eruption recording its effects on structures and people.Methodology/Principal FindingsHere we investigate the causes of mortality in PDCs at Pompeii and surroundings on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
74
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(77 citation statements)
references
References 20 publications
3
74
0
Order By: Relevance
“…11) [25][26][27][28][29][30][31][32] . The limb flexures of the skeletons are typical postures of PDC victims, which result from postmortem shortening of tendons and muscles 33,34 . Statistical documentation of head-tail axes of Confuciusornis carcasses revealed a distinct orientation (E-W) 7,12 , which is consistent with the preferred orientation of victims of PDCs, such as seen in the 1902 Mount Pelée eruptions 33 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…11) [25][26][27][28][29][30][31][32] . The limb flexures of the skeletons are typical postures of PDC victims, which result from postmortem shortening of tendons and muscles 33,34 . Statistical documentation of head-tail axes of Confuciusornis carcasses revealed a distinct orientation (E-W) 7,12 , which is consistent with the preferred orientation of victims of PDCs, such as seen in the 1902 Mount Pelée eruptions 33 .…”
Section: Resultsmentioning
confidence: 99%
“…Vesuvius 34 . Similarly, these characteristics are consistent with experimental results from heating modern bones 34,39 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…That study showed greater difficulty in recovering and analyzing DNA from Herculaneum skeletal remains when compared with molecular analyses of Pompeii bone remains, likely due to exposure to higher thermal stress in the former case (Mastrolorenzo et al, 2001a(Mastrolorenzo et al, , 2010.…”
Section: Introductionmentioning
confidence: 94%
“…Using histochemical techniques, Mastrolorenzo et al (2010) showed the presence of DNA within osteocytic lacunae of bone samples experimentally heated up to 300 °C. Here we test the possibility of extracting and amplifying aDNA from human bone remains of Herculaneum victims showing macro-and microscopic evidence of exposure to temperatures of about 300 °C, using a combination of histological and molecular methods.…”
Section: Introductionmentioning
confidence: 99%